From Ancient Techniques to Modern Solutions: In Situ Synthesis of C‐S‐H for Sandstone Conservation - Mengjun Jia; Huimin Yan; Qingqing Xu; Celestino Grifa; Gang Zhao; Siwei Jiang; Jinhua Wang; Zhenhua Wei; Han Liu; Xiao Ma (Advanced Science)
Abstract Hydraulic calcium‐silicate‐hydrate (C‐S‐H), a key binding agent in both ancient mortars and modern cement, holds significant promise for heritage conservation. Drawing inspiration from ancient Roman techniques, this study investigates the development of C‐S‐H‐based grouting materials to address water‐induced erosive damage in the Beishan Grottoes of the Dazu Rock Carvings. The interfacial interactions between C‐S‐H mortar and sandstone are analyzed using molecular dynamics simulations, revealing the crucial role of hydrogen bonding at the interface of C‐S‐H and mineral phases for adhesion. In the in situ synthesis of C‐S‐H with a reticulated structure from Ca(OH)2/silica fume mixtures under ambient conditions, this work systematically investigates the impact of varying calcium‐to‐silica (C/S) ratio and water‐to‐binder ratios on the mechanical properties and pore structure of C‐S‐H‐based mortars. The optimal mechanical and physical properties are achieved with a C/S ratio of 0.8, water/binder ratio of 2.0, binder/aggregate ratio of 1:3, and 4 wt% polycarboxylate superplasticizer. Laboratory‐scale experiments confirm its excellent compatibility with sandstone, offering a potential effective grouting solution for the Beishan Grottoes and emphasizing the importance of material compatibility in heritage conservation. This integrated approach encompassing materials design, synthesis, characterization, and interfacial analysis, presents a robust framework for developing tailored binding agents for various applications.